The Augmentation Effect of Artificial Intelligence - Vorobeva, Darina (2024)
Vorobeva, D., Pinto, D. C., António, N., & Mattila, A. S. (2024). The Augmentation Effect of Artificial Intelligence: Can AI Framing Shape Customer Acceptance of AI-based Services? Current Issues in Tourism, 27(10), 1551-1571. https://doi.org/10.1080/13683500.2023.2214353 ---%ABS2% ---This work received partial support from national funds through FCT (Fundação para a Ciência e a Tecnologia) , under the project – UIDB/04152/2020 – Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS and 2021.09496.BD.